Humanitarian values in a counterterrorism era. (April 2021) - Modirzadeh, Naz K.; Lewis, Dustin A.
Abstract: In this opinion note, we explore ways to understand the contemporary encounters between a growing global counterterrorism architecture and impartial humanitarian activities while critically assessing our own role in shaping responses to those encounters. Humbled by a decade of experience in this area, we aim to explain how counterterrorism concerns have been elevated over the humanitarian imperative and to offer potential avenues to secure greater respect for impartial humanitarian activities.